2019
DOI: 10.1103/physrevc.100.025801
|View full text |Cite
|
Sign up to set email alerts
|

Thermal quasiparticle random-phase approximation calculations of stellar electron capture rates with the Skyrme effective interaction

Abstract: A microscopic thermodynamically consistent approach is applied to compute electron capture (EC) rates and cross sections on nuclei in hot stellar environments. The cross section calculations are based on the Donnelly-Walecka multipole expansion method for treatment of semi-leptonic processes in nuclei. To take into account thermal effects, we express the electron capture cross section in terms of temperature-and momentum-dependent spectral functions for respective multipole chargechanging operators. The spectr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 61 publications
2
35
0
Order By: Relevance
“…(1) is impossible with current nuclear models. As was shown in [35], within a statistical description the thermalaveraged cross section can be expressed through the temperature-dependent spectral functions for the various momentum-dependent multipole operators derived in [36,37].…”
Section: Electron Capture In the Thermal Qrpa Approachmentioning
confidence: 99%
“…(1) is impossible with current nuclear models. As was shown in [35], within a statistical description the thermalaveraged cross section can be expressed through the temperature-dependent spectral functions for the various momentum-dependent multipole operators derived in [36,37].…”
Section: Electron Capture In the Thermal Qrpa Approachmentioning
confidence: 99%
“…Such schematic calculations, however, tend to have significantly different strength functions even from random phase approximation calculations using realistic shell-model forces [47]. Related thermal QRPA calculations using Skyrme interactions [48][49][50] can also reach highly excited transitions, but may underestimate the total rates due to missing correlations [51]. (In ground state proton-neutron RPA calculations, fragmentation of the Fermi surface due to breaking of axial symmetry can also increase Gamow-Teller strength; furthermore, at least in the lower pf -shell, breaking of rotational symmetries has a stronger effect than breaking particle number in spherical proton-neutron QRPA calculations [52].…”
Section: B a Brief History Of Calculating Astrophysical Weak Rates An...mentioning
confidence: 99%
“…The problem with this approach is the computational burden to reach higher energies. For example, for 49 Cr, which has an M -scheme dimension of only 6 million basis states, the first 100 levels only gets one to 5.5 MeV in excitation energy, and the first 500 levels, which requires about 7000 iterations using thick-restart Lanczos [66], only gets one to 8.28 MeV in excitation energy. While for many astrophysical calculation these initial excitation energies may be sufficient, they also require heroic computational efforts.…”
Section: A Converged Initial States: the Standard Approachmentioning
confidence: 99%
“…Thermal evolution of GT + strengths was presented for 54,56 Fe and 76,78,80 Ge. Recently, the thermal QRPA (TQRPA) approach was used to calculate the electron capture rates for N=50 nuclei and 56 Fe [23,24]. It was shown that thermal excitations can take significant contribution from the GT + strength to electron capture rates.…”
Section: Introductionmentioning
confidence: 99%